PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH PADA MATERI KARAKTERISTIK GEOGRAFIS INDONESIA - Audi Agma Simanjuntak; Ali Fakhrudin; Patricia H.M. Lubis (STKIP Melawi, 2023)
Abstract: Based on observations at SD Negeri 185 Palembang, students are less interested in social studies material, especially in the material of Indonesian Geographical characteristics. This is evidenced by the average score in Theme 1 of 64.16 where the completeness score is 65. In accordance with the 2013 curriculum, teachers must be more creative in developing materials. One of the materials that will be developed is the material on Indonesian Geographical characteristics in class V using Adobe Flash-based learning media. So the purpose of this study is to determine the stages, validity, and development of learning media based on Adobe Flash on the material of Indonesia's geographical characteristics. The method in this study is a research and development method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of this study, development of learning media based on Adobe Flash on the material of Indonesia's geographical characteristics obtained the